Time to Certification of Unions in British Columbia - Holmes, Richard; Rogow, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1994)
The purpose of this paper is to determine the effects of various factors underlying variations in the time taken to certify unions in British Columbia. We employ a multivariate regression model with granting time as the dependent variable and dummy variables for the certification process, unfair labour practice complaints, region, industry union and time period as the independent variables. Size of the union bargaining unit is also considered. Our results show that the certification process is the most important determinant of granting time, and that most of the explanatory power of the model is obtained from the certification process and region regressors.